Sistem Pendidikan di Rusia - Siti Nurrohmah; Agus Faisal Asyha (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to analyze the education system in Russia through a comprehensive examination of historical, philosophical, sociological, geographical, juridical, psychological, educational system, curriculum, and the roles of government and society perspectives. The research employed a qualitative approach using a library research method. Data were collected from various secondary sources, including books, scientific journal articles, official government documents, reports from international organizations, and relevant studies related to the Russian education system. Data analysis was conducted using content analysis techniques through the stages of data collection, reduction, presentation, and conclusion drawing. The findings indicate that the Russian education system has evolved through a long historical process, beginning with the Russian Empire, continuing through the Soviet Union era, and developing further in the modern Russian Federation. Philosophically, Russian education is oriented toward intellectual development, character building, humanism, and patriotism. From a sociological perspective, education functions as a means of social integration within a multiethnic and multicultural society. Geographically, Russia’s vast territory has encouraged the government to promote equal access to education through infrastructure development and the utilization of distance learning technologies. Juridically, education is supported by regulations that guarantee every citizen’s right to obtain quality education. Psychologically, the education system emphasizes the holistic development of students’ potential. The Russian educational structure encompasses formal, non-formal, and informal education, supported by a national curriculum, professional educators, and government policies focused on improving educational quality. Therefore, the Russian education system demonstrates an integrated relationship among policies, curriculum, human resources, and community support in achieving high-quality and globally competitive education.